The Study of the Mutagenic Effect of Carbon Dioxide on Soybean line T-219 (Glycine max (l.) Merrill) (Eurasian Journal of Ecology, 2019)
The mutagenic activity of carbon dioxide (CO2) on the mutant soybean line T-219 (Glycine max(L.) Merrill), in which the synthesis of chlorophyll depends on the allelic state of the gene, was studied.The dominant allele Y11 causes a dark green plant, and the recessive allele y11 causes a golden yellowplant. We examined the level of somatic mutations by the presence of light green spots on dark greenleaves and yellow spots on light green leaves (direct mutation Y11 → y11), light green spots on goldenyellow leaves (reverse mutation y11 → Y11). Methyl methanesulfonate (MMS), a direct-acting mutagen,was used as a positive control. Soybean seeds, treated with MMS for 24 hours, were germinated understandard laboratory conditions and conditions of high CO2 concentration (5000 ppm) in a specializedbox with adjustable CO2 content. In plants grown under high CO2 concentration, the frequency of leafsomatic mutations was at the control level. However, in plants whose seeds were treated in MMS andgrown under standard laboratory conditions, the total number of spots per leaf statistically significantlyincreased 4.3 times (p